The Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale: A New Instrument for Assessing the Anxiety Response of General Population to the Viral Epidemic During the COVID-19 Pandemic - Chung, Seockhoon; Ahn, Myung Hee; Lee, Sangha; Kang, Solbi; Suh, Sooyeon; Shin, Yong-Wook (Frontiers in Psychology, 2021)
People have reported experiencing anxiety due to the COVID-19 pandemic. This study explored the validity and usefulness of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale for measuring the general population’s anxiety response to the viral epidemic. About 1,009 respondents participated in an online survey. Of these, 501 (49.7%) participants were rated as having at least a mild degree of anxiety response to the viral epidemic (SAVE-6 score ≥ 15), whereas 90 (8.9%) and 91 (9.0%) were rated as having depression and anxiety, respectively. The SAVE-6 scale showed good internal consistency (Cronbach’s α = .82). Confirmatory factor analysis supported a one-factor structure for the measure. Goodness-of-fit indices (χ2/df ratio = 19.1, CFI = .92; TLI = .86; SRMR = 0.05; RMSEA = .13) were adequate. The SAVE-6 scale was found to be a reliable, valid, and useful brief measure that can be applied to the general population. The SAVE-6 scale is useful for easily assessing the anxiety symptoms during the pandemic in the general population.